If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(u + 8) + -8u = 22 Reorder the terms: 5(8 + u) + -8u = 22 (8 * 5 + u * 5) + -8u = 22 (40 + 5u) + -8u = 22 Combine like terms: 5u + -8u = -3u 40 + -3u = 22 Solving 40 + -3u = 22 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-40' to each side of the equation. 40 + -40 + -3u = 22 + -40 Combine like terms: 40 + -40 = 0 0 + -3u = 22 + -40 -3u = 22 + -40 Combine like terms: 22 + -40 = -18 -3u = -18 Divide each side by '-3'. u = 6 Simplifying u = 6
| 180=(3x+8)+(7x-18) | | 1+x=-2*8 | | 3(3n+4)=36+6n | | 0.5(8k+2)=17 | | 7+5ln(x)=2 | | (3b+2r)+(4b+r)= | | H=(6x-10) | | h(10)=x^2-9 | | 16f+4g= | | -45=-4x+11 | | 160=-8p-5(1+5p) | | 4(t+u)=19 | | 14x+18=126 | | X^2/-2 | | -3+x=-8*-3 | | 2(1.3-3)=2.6-5 | | .75x=350000 | | .4*x=38 | | X^2/10 | | 9(3-2x)=2(-8+10) | | 11x^2-82x+147=0 | | (3x+17)+(x-23)=9 | | 5x^4-44x^2+22=0 | | 2.5X+2.5X=10 | | g(3)=3x^2+1 | | 9(d-4)-8+2d=5d-4+2d | | 4x=(20x-8) | | X=25.6+-1.4Y | | (3x+17)+(4x-5)=90 | | 5+2(x)=3(x)-2 | | 0.6=0.5+25 | | 0.25X+0.35Y=6.4 |